On Generalized Holder's Inequality in Weak Morrey Spaces - Wajih, Asyraf; Gunawan, Hendra (Journal of the Indonesian Mathematical Society, 2020)
In this paper we reprove generalized Hölder's inequality in weak Morrey spaces. In particular, we get sharper bounds than those in \cite{gunawan2}. The bounds are obtained through the relation of weak Morrey spaces and weak Lebesgue spaces.